2021
DOI: 10.1007/s10237-021-01492-y
|View full text |Cite
|
Sign up to set email alerts
|

Architectural model for muscle growth during maturation

Abstract: Muscle architecture, which includes parameters like fascicle length, pennation angle, and physiological cross-sectional area, strongly influences skeletal muscles' mechanical properties. During maturation, the muscle architecture has to adapt to a growing organism. This study aimed to develop an architectural model capable of predicting the complete 3D fascicle architecture for primarily unipennate muscles of an arbitrary age, based on fascicle data for an initial age. For model development, we collected novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In rat parallel fibered muscles, growth is only determined by longitudinal muscle fiber growth (Willems and Huijing, 1992), while in pennate muscles of rats and ducks, longitudinal muscle growth also occurs by radial growth of muscle fibers (Swatland, 1980;Woittiez et al, 1986;Papenkort et al, 2020). During development, muscle PCSA increases (Woittiez et al, 1986(Woittiez et al, , 1989de Koning et al, 1987;Papenkort et al, 2020Papenkort et al, , 2021 by an increase in fCSA (Swatland, 1980;Alnaqeeb and Goldspink, 1987;Willems and Huijing, 1992). Although some studies (e.g., Enesco and Puddy, 1964;Ross et al, 1987) have reported hyperplasia during postnatal development in rat muscles, more have shown that hyperplasia does not occur in muscles from rodents (Goldspink, 1972;Timson and Dudenhoeffer, 1990;White et al, 2010).…”
Section: Animal Experimentation Typical Muscle Growth In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In rat parallel fibered muscles, growth is only determined by longitudinal muscle fiber growth (Willems and Huijing, 1992), while in pennate muscles of rats and ducks, longitudinal muscle growth also occurs by radial growth of muscle fibers (Swatland, 1980;Woittiez et al, 1986;Papenkort et al, 2020). During development, muscle PCSA increases (Woittiez et al, 1986(Woittiez et al, , 1989de Koning et al, 1987;Papenkort et al, 2020Papenkort et al, , 2021 by an increase in fCSA (Swatland, 1980;Alnaqeeb and Goldspink, 1987;Willems and Huijing, 1992). Although some studies (e.g., Enesco and Puddy, 1964;Ross et al, 1987) have reported hyperplasia during postnatal development in rat muscles, more have shown that hyperplasia does not occur in muscles from rodents (Goldspink, 1972;Timson and Dudenhoeffer, 1990;White et al, 2010).…”
Section: Animal Experimentation Typical Muscle Growth In Animalsmentioning
confidence: 99%
“…In an almost completely parallel fibered muscle (i.e., semimembranosus lateralis of the rat), the fiber PA has been found to increase during development (Willems and Huijing, 1992). In pennate muscles of growing rats and rabbits (GM) and rabbits (soleus and plantaris muscles), it seems that the PA increases only slightly during growth (Heslinga and Huijing, 1990;Papenkort et al, 2020Papenkort et al, , 2021. Note that changes in PA over age may differ between muscle types (cf.…”
Section: Animal Experimentation Typical Muscle Growth In Animalsmentioning
confidence: 99%
“…FCSA and SF depend on the accuracy of the cryostat cuts since these parameter's values could be altered with changes on the sample orientation in the cryostat and also due to the 3D muscle fibre architecture. The line of action between muscle insertion and its origin is different depending on the level where cuts were done due to differences in fibre length, pennation angle and curvature (Papenkort et al, 2020 ; Stark & Schilling, 2010 ; Wick et al, 2018 ). This intramuscular architecture entails different fibre morphometrical measurements along the proximal, equatorial or distal muscle level (Torrella et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the right gastrocnemius are shown in white boxes and data from the left gastrocnemius in grey boxes. p-values resulting from statistical comparisons between right and left muscles after running paired t-Student tests are shown for each muscle zone on the graph fibre length, pennation angle and curvature(Papenkort et al, 2020;…”
mentioning
confidence: 99%
“…While the architecture of any particular muscle is broadly similar across individuals, muscle architecture can adapt to exercise (Alonso-Fernandez et al, 2018; Blazevich et al, 2003;Roig et al, 2008), ageing (Narici et al, 2003;Papenkort et al, 2021;Shur et al, 2021;Siebert et al, 2017) and disease (Bodine et al, 1982; Fahn-Lai et al, 2020; Kruse et al, 2018; J. E. Park et al, 2019). Quantitative measurement of muscle-and subject-speci c architecture is therefore useful for the study of muscle adaptation and muscle dysfunction.…”
Section: Introductionmentioning
confidence: 99%